The metaphysics of creation : Aquinas's natural theology in Summa contra gentiles II - Kretzmann, Norman (Clarendon Press ; Oxford University Press, 1999)
Norman Kretzmann expounds and criticises Aquinas' theology of creation, which is natural (or philosophical) in that Aquinas developed it without depending on the data of Scripture.